THE RELATIONSHIP BETWEEN SELF-EFICACY AND LEARNING MOTIVATION OF GRADE X STUDENTS AT MAN 5 CIAMIS 2026 - Fikri Fadilah*; Yandi Cahya Yundani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Learning motivation is a crucial aspect in supporting student success in school. However, in reality, many students still exhibit behaviors lacking in learning motivation, such as procrastinating on assignments, not focusing when the teacher explains, being unable to complete assignments, and lacking enthusiasm for their learning. The purpose of this study was to determine the relationship between self-efficacy and learning motivation in grade 10 students at MAN 5 Ciamis. The approach used was quantitative, employing the associative method. The population of 130 grade 10 students at MAN 5 Ciamis was determined at 98 using the Slovin formula and simple random sampling technique. The instrument used was a questionnaire with Likert scale scoring. Data analysis used validity tests, reliability tests, descriptive analysis, linearity tests, and Person-Product-Moment correlations. Based on the results of the data analysis, the average student self-efficacy score was 56.12. The average learning motivation score was 55.87. The correlation results indicate a strong relationship between self-efficacy and learning motivation, with an r value of 0.753 and a significance level of 0.000. Based on these results, it can be concluded that self-efficacy has a strong relationship with learning motivation in grade 10 students at MAN 5 Ciamis.